2013
DOI: 10.1007/s10964-013-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Friend Affiliations and School Adjustment Among Mexican-American Adolescents: The Moderating Role of Peer and Parent Support

Abstract: Studies examining friendships among Mexican-American adolescents have largely focused on their potentially negative influence. The current study examined the extent to which deviant and achievement-oriented friend affiliations are associated with Mexican-American adolescents’ school adjustment and also tested whether support from friends and parents moderates these associations. High school students (N = 412; 49 % male) completed questionnaires and daily diaries; primary caregivers also completed a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
1
23
0
3
Order By: Relevance
“…These different peer relationships influence adolescents' academic and behavioral adjustment in different but interrelated ways (Kindermann & Skinner, ). The characteristics of one's friends and peer group are important determinants of adolescents' academic motivation and achievement (Espinoza, Gillen‐O'Neel, Gonzales, & Fuligni, ; Wang & Eccles, ). For example, middle school students who perceived their friends as positively engaged in school increased in their own positive school involvement from the fall to the spring of the year (Berndt & Keefe, ).…”
Section: Student Engagement In Early Adolescencementioning
confidence: 99%
See 2 more Smart Citations
“…These different peer relationships influence adolescents' academic and behavioral adjustment in different but interrelated ways (Kindermann & Skinner, ). The characteristics of one's friends and peer group are important determinants of adolescents' academic motivation and achievement (Espinoza, Gillen‐O'Neel, Gonzales, & Fuligni, ; Wang & Eccles, ). For example, middle school students who perceived their friends as positively engaged in school increased in their own positive school involvement from the fall to the spring of the year (Berndt & Keefe, ).…”
Section: Student Engagement In Early Adolescencementioning
confidence: 99%
“…Studies examining the effects of parent affective support and friends' school involvement and achievement also report interactive effects on school engagement and educational aspirations (Marion, Laursen, Kiuru, Nurmi, & Salmela‐Aro, ). In a study of Mexican American adolescents, affiliating with friends with low academic orientation was associated with lower educational aspirations only among adolescents who reported low levels of parental warmth (Espinoza et al., ).…”
Section: Student Engagement In Early Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…Itxaropen akademikoei dagokienez, literatura zientifikoan desberdintasun nabarmenak frogatzen dira emakumeen alde nerabezaroan (Antonio-Agirre et al, 2015;Droguett, 2011;Espinoza, Gillen-O'Neel, Gonzales, eta Fuligni, 2014;Heras eta Navarro, 2012;Suárez-Álvarez et al, 2014). Hain zuzen ere, badira ikerketa batzuk non irakasleek nesken itxaropen akademikoak positiboago azaltzen baitituzte (Cava eta Musitu, 1999a).…”
Section: Desberdintasunak Sexuaren Araberaunclassified
“…Prior research may support parental fears about their adolescent children's friendships; associating with deviant peers can certainly be detrimental for adolescent outcomes. However, research has also indicated that peer influences on adolescent behavior are often problematic only when parental support and management are low (Dishion et al 2004;Espinoza et al 2014). On the other hand, research suggests that both parents and school/peers provide adolescents with vital forms of social capital (Crosnoe 2004;Reynolds 2006;Zhou and Bankston 2001) and parental efforts to keep their children safe may deprive them of social capital derived from other sources.…”
Section: Implications Of Preventing Children's Friendshipsmentioning
confidence: 99%